ALLOLOBOPHORA BIOKOVICA sp. n. (Oligochaeta: Lumbricidae) AND EARTHWORM ASSOCIATIONS OF THE BIOKOVO (CROATIA) - N. Mršić (Acta Biologica Slovenica)
The author describes a new species Allolobophora biokovica sp.n., a new species Dendrobaena bokakotorensis Šapkarev 1975 for the Croatian fauna and presents data on other earthworm species found on the Biokovo. He analyses 5 earthworm associations of the Biokovo and compares them with other classified earthworm associations in other parts of Yugoslavia. A biogeographic analysis of the Biokovois also included.